Why (not) arrest? Third-party state compliance and noncompliance with international criminal tribunals. Issue 4 (1st October 2016) - Berlin, Mark S.
ABSTRACT: Why do some states comply with their legal obligations to arrest suspects indicted by international criminal tribunals (ICTs) while others do not? Research on this question has mostly focused on "target" states, like the former Yugoslav republics, where ICTs have intervened. In contrast, this article offers the first test of theories regarding ICT arrest-warrant compliance and noncompliance by third-party states . I examine the International Criminal Tribunal for Rwanda (ICTR) and 26 third-party states implicated in the pursuit of the court's 91 indicted suspects. Using fuzzy-set qualitative comparative analysis, I find support for the procompliance influence of liberal democratic norms and foreign aid dependency on third-party states. I also find that non compliance — something existing studies tend to leave untheorized — can be explained by the presence of either non- compliance constituencies or high official corruption. By testing several theories of compliance and noncompliance on a so far understudied class of cases, these findings provide support for the generalizability of a number of explanations in the broader literature on compliance with human rights obligations. The analysis also shows that problematizing noncompliance — and not merely reducing it to an absence of procompliance factors — can help us develop fuller explanations of compliance behavior.